Application of Laplace Transform on Fractional Kinetic Equation Pertaining to the Generalized Galué Type Struve Function. (4th June 2019) - Habenom, Haile; Suthar, D. L.; Gebeyehu, Melaku
Abstract : In this paper, we establish extensive form of the fractional kinetic equation involving generalized Galué type Struve function using the technique of Laplace transforms. The results are expressed in terms of Mittag-Leffler function. Further, numerical values of the results and their graphical interpretation are interpreted to study the behaviour of these solutions. The results obtained here are quite general in nature and capable of yielding a very large number of known and (presumably) new results.